2010
DOI: 10.1128/cvi.00311-10
|View full text |Cite|
|
Sign up to set email alerts
|

The Th1 Immune Response toPlasmodium falciparumCircumsporozoite Protein Is Boosted by Adenovirus Vectors 35 and 26 with a Homologous Insert

Abstract: The most advanced malaria vaccine, RTS,S, is comprised of an adjuvant portion of the Plasmodium falciparum circumsporozoite (CS) protein fused to and admixed with the hepatitis B virus surface antigen. This vaccine confers short-term protection against malaria infection, with an efficacy of about 50%, and induces particularly B-cell and CD4؉ T-cell responses. In the present study, we tested by the hypothesis that the Th1 immune response to CS protein, in particular the CD8 ؉ T-cell response, which is needed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 57 publications
(69 reference statements)
3
47
0
Order By: Relevance
“…ELISA reactivity suggested that IgG1 was initially produced more than IgG2a, though levels were very similar at week 14 after boost. Other authors have also observed a preferential induction of antibodies of the IgG1 subclass when vaccinating with Montanide ISA720, in both mice (41) and humans (3). The induction of not only IgG1 but also IgG2a responses is important, since in malaria, as in all infectious diseases, antibody isotypes affect pathogen neutralization and clearance, and it is widely accepted that cytophilic antibodies (such as mouse IgG2a) are involved in protective immunity against Plasmodium AMA-1 and other blood-stage antigens (22,36).…”
Section: Discussionmentioning
confidence: 71%
“…ELISA reactivity suggested that IgG1 was initially produced more than IgG2a, though levels were very similar at week 14 after boost. Other authors have also observed a preferential induction of antibodies of the IgG1 subclass when vaccinating with Montanide ISA720, in both mice (41) and humans (3). The induction of not only IgG1 but also IgG2a responses is important, since in malaria, as in all infectious diseases, antibody isotypes affect pathogen neutralization and clearance, and it is widely accepted that cytophilic antibodies (such as mouse IgG2a) are involved in protective immunity against Plasmodium AMA-1 and other blood-stage antigens (22,36).…”
Section: Discussionmentioning
confidence: 71%
“…These pre-existing Ad5 nAb impair the immunogenicity of Ad5-based vaccines in animal models and in humans (3,(8)(9)(10) and may also potentially compromise their safety (11). For these reasons, other human Adenovirus (Ad) vectors based on rare serotypes such as Ad11, Ad24, Ad26, Ad34, Ad35, Ad48, Ad49, and Ad50 have been proposed as potential alternatives to Ad5 because they are rarely neutralised by antibodies present in humans, and are currently being evaluated in a number of pre-clinical and clinical studies (12)(13)(14)(15)(16). However, successful development of Ad vectors as genetic vaccine carriers will eventually depend not only on the low frequency of nAb present in the target population (seroprevalence), but also on their immunological potency as well as other characteristics including good biological tractability and availability of cell substrates approved by regulators for efficient manufacturing and scalable and reproducible production processes.…”
Section: Introductionmentioning
confidence: 99%
“…To extend this finding to our assay setup, a selected number of samples was tested in an ELISA using recombinant CS protein as capture antigen. This CS protein batch was produced on Hansenula polymorpha yeast for research purposes (13); however, the quantity of this protein source system cannot be continuously guaranteed for it to be a reliable source of antigen in a standard assay. Figure 3 shows the correlation between the two techniques.…”
Section: Resultsmentioning
confidence: 99%